UV-SPECTROPHOTOMETRIC METHOD DEVELOPMENT AND VALIDATION FOR ESTIMATION OF SAXAGLIPTIN IN API AND PHARMACEUTICAL DOSAGE FORM - SHINDE, BHAGYASHRI S.; KALSHETTI, M. S.; KOKANE, ANJALI P. (International Journal of Current Pharmaceutical Research, 2020)
Objective: A new sensitive, economical, simple, rapid UV spectrophotometric method has been developed for the estimation of Saxagliptin in API and pharmaceutical formulation. Methods: Calibration curve method was used for the estimation of Saxagliptin in API and pharmaceutical formulation. Results: The method was validated for linearity, range, accuracy, precision, robustness, LOD, LOQ. Linearity was found in the range of 10-60µg/ml. Accuracy was performed by using a recovery study. The amount of drug recovered was found to be in the range of 99.01-100.1%. All the parameters were validated as per the ICH guidelines. Conclusion: This method is suitable forused routine analysis of present Saxagliptin in API and Pharmaceutical dosage form.